Comparison of the cone-tracing simulation and the room impulse response measurements - PĘKALA, P. (Archives of Acoustics, 2006)
The experimental verification of the acoustic field model based on the cone-tracing method [1, 2] is described. With simulated echograms and the impulse responses obtained experimentally, a set of parameters: Early Decay Time (EDT), C50 and C80 were obtained. The parameters measured at many receiving sites and those calculated were compared. Mean differences of less than 2 dB were observed for the octave band mid-frequencies above 125 Hz.